2018
DOI: 10.1111/evj.12956
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral cervical plexus block for prosthetic laryngoplasty in the standing horse

Abstract: For standing unilateral laryngeal surgery, a cervical plexus block is a viable alternative to tissue infiltration and it improves the surgical field conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…The risk avoidance of general anesthesia and recovery is cited as a major benefit in the advent of the standing prosthetic laryngoplasty (20). Indeed, standing surgery does not require anesthetic recovery, but standing laryngoplasty is performed under sedation using α2-adrenergic receptor agonists as either intermittent boluses or a constant rate infusion (11,20). A recent study comparing fecal output and postoperative colic in horses undergoing standing or general anesthesia showed that horses with higher cumulative doses of detomidine had a longer time to first fecal passage and reduced overall 24-h fecal output.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The risk avoidance of general anesthesia and recovery is cited as a major benefit in the advent of the standing prosthetic laryngoplasty (20). Indeed, standing surgery does not require anesthetic recovery, but standing laryngoplasty is performed under sedation using α2-adrenergic receptor agonists as either intermittent boluses or a constant rate infusion (11,20). A recent study comparing fecal output and postoperative colic in horses undergoing standing or general anesthesia showed that horses with higher cumulative doses of detomidine had a longer time to first fecal passage and reduced overall 24-h fecal output.…”
Section: Discussionmentioning
confidence: 99%
“…The ventral branch of C2 and the cutaneous branches of C3 do not provide sensory innervation to the deeper laryngeal structures. During standing prosthetic laryngoplasty, a second intraoperative local anesthetic infiltration at the level of the caudal pharyngeal constrictors and cricoarytenoid joint is necessary for antinociception (11). Albeit rare, anecdotal transient contralateral arytenoid paresis/plegia has been observed during standing prosthetic laryngoplasty due to local anesthetic diffusion leading to inadvertent blockade of the contralateral recurrent laryngeal nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine publications focused on different loco-regional techniques [272][273][274][275][276][277][278][279][280]. In the last few years, a renaissance of loco-regional techniques on standing horses has occurred with the advent of ultrasound guided technology [469,470]. When general anaesthesia is unavoidable, loco-regional techniques can still be used to provide intra-and postoperative analgesia, reduce surgical stimulations and produce muscle relaxation.…”
Section: Other Drugs Used During Maintenancementioning
confidence: 99%